Chromium distribution in shoots of macrophyte Callitriche cophocarpa Sendtn. - Augustynowicz, Joanna (Springer Berlin Heidelberg, 2014)
The aim of the study was the analysis of Cr distribution in shoots of the macrophyte Callitriche cophocarpa by means of two X-ray-based techniques: micro X-ray fluorescence (μXRF) and electron probe X-ray microanalysis (EPXMA). Plants were treated with 100 μM (5.2 mg l(−1)) chromium solutions for 7 days. Cr was introduced independently at two speciations as Cr(III) and Cr(VI), known for their diverse physicochemical properties and different influence on living organisms. A comparative analysis of Cr(III)-treated plants by EPXMA and μXRF demonstrated high deposition of Cr in epidermal glands/hairs localized on leaves and stems of the plant shoots. Cr in Cr(III)-treated plants was recorded solely in glands/hairs, and the element was not present in any other structures. On the other hand, Cr in Cr(VI)-treated group of plants was rather found in vascular bundles. Moreover, the concentration of Cr in Cr(VI)-treated plants was significantly lower than in plants incubated in Cr(III) solution. The results obtained in this work suggest differences in chromium uptake, transport and accumulation dependent on the oxidative state of the element.